Lung cancer survival among Florida male firefighters - Koru-Sengul, Tulay; Pinheiro, Paulo S.; Zhao, Wei; Hernandez, Monique N.; Hernandez, Diana R.; Maggioni, Alessandra; Kobetz, Erin N.; Caban-Martinez, Alberto J.; Lee, David J. (Frontiers in Oncology, 2023)
Introduction Lung cancer is a leading cause of cancer incidence and death in the United States. Although most firefighters are fit and do not smoke, they are exposed to many known carcinogens during and in the aftermath of firefighting activities. Comprehensive epidemiologic investigations on lung cancer survival for both career and volunteer firefighters have not been undertaken. Methods Data from the Florida Cancer Data System (1981–2014) were linked with firefighter certification records from the Florida State Fire Marshal’s Office to identify all patients of this occupational group; lung cancer cause-specific survival data were compared with other occupational groups using Cox regression models with occupation as the main effect. Adjusted hazard ratios (aHR) and 95% confidence intervals (95% CI) were calculated. Results Out of 210,541 male lung cancer cases diagnosed in Florida (1981–2014), 761 were firefighters (604 career, 157 volunteer). Lung cancer death was similar between volunteer (75.2%) and career firefighters (74.0%) but lower than non-firefighters (80.0%). Survival at 5 years was higher among firefighters (29.7%; career: 30.3%; volunteer: 27.4%) than non-firefighters (23.8%). In a multivariable model, compared with non-firefighters, firefighters have significantly higher cause-specific survival (aHR = 0.84; 95% CI: 0.77–0.91; p < 0.001). However, there were no significant survival differences between career and volunteer firefighters (1.14; 0.93–1.39; p = 0.213). In a separate multivariable model with firefighters as the comparator, other broad occupational groups had significantly lower cause-specific survival [white collar: 1.11 (1.02–1.21); blue collar: 1.15 (1.05–1.25); service: 1.13 (1.03–1.25); others/unknown: 1.21 (1.12–1.32); all p-values < 0.02]. Conclusion Lung cancer survival is significantly higher among firefighters compared with non-firefighters, but there is no significant difference between career and volunteer firefighters. Improved survival for firefighters might be due to a healthy worker effect, lower smoking prevalence relative to other worker groups, and possibly superior treatment adherence and compliance. Many firefighters are cross-trained as EMTs/paramedics and possess a level of medical knowledge that may favorably impact treatment engagement and better navigation of complex cancer care.